Controlled transdermal iontophoresis of sulfosalicylic acid from polypyrrole/poly(acrylic acid) hydrogel - Phithupha Chansai (2018)
A conductive polymer-hydrogel blend between sulfosalicylic acid-doped polypyrrole (PPy) and poly(acrylic acid) (PAA) was used as a carrier/matrix for the transdermal drug delivery under applied electrical field. PAA films and the blend films were prepared by solution casting with ethylene glycol dimethacrylate (EGDMA) as a cross-linking agent, followed by the blending of PPy particles and the PAA matrix. The effects of cross-linking ratio and electric field strength on the diffusion of the drug from PAA and PPy/PAA hydrogels were investigated using a modified Franz-diffusion cell with an acetate buffer of pH 5.5 and at 37 °C, for a period of 48 h. The diffusion coefficient of the drug is calculated using the Higuchi equation, with and without an electric field, at various cross-linking ratios. The drug diffusion coefficient decreases with increasing drug size/mesh size ratio, irrespective of the presence of the conductive polymer as the drug carrier. The diffusion coefficient, at the applied electric field of 1.0 V, becomes larger by an order of magnitude relative to those without the electric field. © 2009 Elsevier B.V. All rights reserved.